2020
DOI: 10.1126/sciadv.aba9966
|View full text |Cite
|
Sign up to set email alerts
|

Water-ion permselectivity of narrow-diameter carbon nanotubes

Abstract: Carbon nanotube (CNT) pores, which mimic the structure of the aquaporin channels, support extremely high water transport rates that make them strong candidates for building artificial water channels and high-performance membranes. Here, we measure water and ion permeation through 0.8-nm-diameter CNT porins (CNTPs)—short CNT segments embedded in lipid membranes—under optimized experimental conditions. Measured activation energy of water transport through the CNTPs agrees with the barrier values typical for sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 63 publications
3
83
1
Order By: Relevance
“…Furnished with carboxyl groups at their ends, tube partitioning into the lipid bilayer is facilitated at low pH values since protonation of these groups renders them electrically neutral. A subsequent study reported a lower E A of only 5.3 kcal/mol (Li et al 2020). Since it neither investigated the pH-dependence of water flow nor cation permeation, their transport pathways remain elusive.…”
Section: Single-file Water Transport and Selectivity In Artificial Channelsmentioning
confidence: 98%
See 1 more Smart Citation
“…Furnished with carboxyl groups at their ends, tube partitioning into the lipid bilayer is facilitated at low pH values since protonation of these groups renders them electrically neutral. A subsequent study reported a lower E A of only 5.3 kcal/mol (Li et al 2020). Since it neither investigated the pH-dependence of water flow nor cation permeation, their transport pathways remain elusive.…”
Section: Single-file Water Transport and Selectivity In Artificial Channelsmentioning
confidence: 98%
“…Thus, the plot indicates a negligible entropy of activation for water diffusion across lipid bilayers and membrane channels. Below, we list the sources of the plotted data next to the abbreviations used in the figure: aquaporin-1, AQP1 (Horner et al 2015;Zeidel et al 1992); aquaporin-Z, AQPZ (Horner et al 2015;Pohl et al 2001); bacterial potassium channel, KcsA (Horner et al 2015;Saparov and Pohl 2004); gramicidin A, gA (Pohl and Saparov 2000;Boehler et al 1978); aquaporin-0, AQP0 (Zampighi et al 1995;Kumar et al 2012); palmitoyl oleoyl phosphatidylcholine, POPC (Huster et al 1997); dioleoyl phosphatidylcholine, DOPC (Huster et al 1997); polar lipid extract from Escherichia coli, E. coli PLE (Saparov and Pohl 2004;Pluhackova and Horner 2021); egg and plant phosphatidylcholine, Egg PC and Plant PC (Fettiplace and Haydon 1980); CNT, CN-1 (Tunuguntla et al 2017); CNT, CN-2 (Li et al 2020); aquafoldamer, AQF (Shen et al 2020).…”
Section: • •mentioning
confidence: 99%
“…water forming four H-bonds in bulk water 54,55 , the activation energies can be estimated to be 6.1, 6.3 and 4.1 kcal/mol for 3-LA, 4-LA and AQP1, respectively. These values are consistent with their respective experimental activation energies of 8.7, 8.3 and 5.0 kcal/mol.…”
Section: Simulation Of Water Transport and Proton Rejection Mechanismmentioning
confidence: 99%
“…This knowledge is exquisitely important for the design of artificial channels [21][22][23][24][25][26][27] in material science, where the selectivity and permeability mechanism of AQPs serve as template to design artificial water channels envisioned to be used in next generation membrane-based separations and purifications. Similarly, AQPs [28][29][30][31][32][33][34][35] itself or carbon nanotubes 36 are envisioned as building blocks of biomimetic membranes. These highly permeable pore structures are envisioned to determine membrane performance, selectivity and functionality.…”
Section: Introductionmentioning
confidence: 99%